Understanding a mechanism between perceived discrimination and obesity among Latinas in the United States. Issue 4 (19th May 2021) - Ai, Amy L.; Lee, Jungup
ABSTRACT: Objective: Obesity is a prominent public health concern significantly impacting various minority groups, especially Latina Americans. However, little study has explored acculturation-related factors associated with obesity among Latinas in the United States. This study examines the link between acculturation-related factors and obesity among Latinas. Design: Using the National Latino and Asian American Study (NLAAS), we detected the incremental associations of acculturation-related factors, especially perceived discrimination with obesity, after controlling for socio-demographics, among all 1427 Latinas. Two-step logistic regression analyses were conducted to investigate the association. Results: Results indicated perceived discrimination and older age were positively associated with Latinas' obesity. Conversely, income and acculturation stress were negatively associated with obesity. Further, results revealed a significant moderating effect of education on the association between perceived discrimination and obesity. Conclusion: The findings suggest the need for clinical attention towards socio-cultural influences and ethnic backgrounds in obesity assessment and intervention.